Characterization of chicken burger prepared with pequi flour (Research, Society and Development, 2022)
The pequi, a yellow fruit native to the Brazilian Cerrado, has nutritional characteristics of great interest to the food industry. The present study aims to incorporate different concentrations of pequi flour into chicken burgers, evaluating its composition and its physical and technological properties. Therefore, analyses of centesimal composition, hydrogen potential (pH), water activity (Aw), instrumental color and texture and cooking loss (PPC) were performed. The parameters: water activity (Aw), adhesiveness, cohesiveness and flexibility did not present significant differences (p